Explaining covid-19 performance: what factors might predict national responses?. (28th January 2021) - Baum, Fran; Freeman, Toby; Musolino, Connie; Abramovitz, Mimi; De Ceukelaire, Wim; Flavel, Joanne; Friel, Sharon; Giugliani, Camila; Howden-Chapman, Philippa; Huong, Nguyen Thanh; London, Leslie; McKee, Martin; et al.
Abstract : Correspondence to: F Baum fran.baum@flinders.edu.au Fran Baum and colleagues discuss the factors that affected prediction of the success of national responses to covid-19 and will influence future pandemic preparedness